Reduced neural responsiveness to looming stimuli is associated with increased aggression. Issue 10 (7th May 2021) - Blair, R James; Zhang, R u; Bashford-Largo, Johannah; Bajaj, Sahil; Mathur, Avantika; Ringle, Jay; Schwartz, Amanda; Elowsky, Jaimie; Dobbertin, Matthew; Blair, Karina S; Tyler, Patrick M
Abstract: While neuro-cognitive work examining aggression has examined patients with conditions at increased risk for aggression or individuals self-reporting past aggression, little work has attempted to identify neuro-cognitive markers associated with observed/recorded aggression. The goal of the current study was to determine the extent to which aggression by youth in the first three months of residential care was associated with atypical responsiveness to threat stimuli. This functional MRI study involved 98 (68 male; mean age = 15.96 [sd = 1.52]) adolescents in residential care performing a looming threat task involving images of threatening and neutral human faces or animals that appeared to be either loom or recede. Level of aggression was negatively associated with responding to looming stimuli (irrespective of whether these were threatening or neutral) within regions including bilateral inferior frontal gyrus, right inferior parietal lobule, right superior/middle temporal gyrus and a region of right uncus proximal to the amygdala. These data indicate that aggression level is associated with a decrease in responsiveness to a basic threat cue-looming stimuli. Reduced threat responsiveness likely results in the individual being less able to represent the negative consequences that may result from engaging in aggression, thereby increasing the risk for aggressive episodes.